Blockchain Technology in Energy Management Systems: Enhancing Security and Transparency - Varshney Neeraj; Sreetharan V.; Vennila C.; Ahila R.; Mane Deepak T.; Kshirsagar Kundalik; Pragathi B. (E3S Web of Conferences)
Blockchain technology provides considerable promise to enhance security and transparency in energy management systems. As energy systems grow decentralized and involve various stakeholders, challenges including data integrity, transaction security, and transparency are becoming crucial. Traditional energy systems have risks such as cyberattacks, data manipulation, and inefficiencies owing to centralized control. Blockchain’s decentralized, immutable, and transparent ledger system can overcome these difficulties by enabling safe, verifiable, and tamper-proof energy transactions. Smart contracts further automate and ensure trust in energy trades. This article analyzes blockchain’s application in energy management systems, concentrating on decentralized energy trade, real-time grid balancing, and transparent billing. It also addresses the security implications of blockchain, its limitations, and future potential. While scalability and energy efficiency challenges persist, blockchain's role in constructing more resilient, secure, and transparent energy infrastructures shows promise for the future of energy management.